XocR, a LuxR solo required for virulence in Xanthomonas oryzae pv. oryzicola - Xu, Huiyong; Yancun, Zhao; Qian, Guoliang; Liu, Fengquan (Frontiers in Cellular and Infection Microbiology, 2015)
Xanthomonas oryzae pv. oryzicola (Xoc) causes bacterial leaf streak (BLS) in rice, a serious bacterial disease of rice in Asia and parts of Africa. The virulence mechanisms of Xoc are not entirely clear and control measures for BLS are poorly developed. The solo LuxR proteins are widespread and shown to be involved in virulence in some plant associated bacteria (PAB). Here, we have cloned and characterized a PAB LuxR solo from Xoc, named as XocR. Mutation of xocR almost completely impaired the virulence ability of Xoc on host rice, but did not alter the ability to trigger HR (hypersensitive response, a programmed cell death) on non-host (plant) tobacco, suggesting the diversity of function of xocR in host and non-host plants. We also provide evidence to show that xocR is involved in the regulation of growth-independent cell motility in response to a yet-to-be-identified rice signal, as mutation of xocR impaired cell swimming motility of wild-type Rs105 in the presence but not absence of rice macerate. We further found that xocR regulated the transcription of two characterized virulence-associated genes (recN and trpE) in the presence of rice macerate. The promoter regions of recN and trpE possessed a potential binding motif (an imperfect pip box-like element) of XocR, raising the possibility that XocR might directly bind the promoter regions of these two genes to regulate their transcriptional activity. Our studies add a new member of PAB LuxR solos and also provide new insights into the role of PAB LuxR solo in the virulence of Xanthomonas species.